Network topological reorganization mechanisms of primary visual cortex under multimodal stimulation - Li, Zhen; Peng, Zhiyong; He, LiHua; Zhu, Xuan; Hu, Dewen; Li, Ming (Frontiers in Neuroscience, 2025)
IntroductionThe functional connectivity topology of the primary visual cortex (V1) shapes sensory processing and cross-modal integration, yet how different sensory modalities reorganize V1 network architecture remains unclear. We hypothesized that multimodal input drives a shift from hub-centric, modular processing toward globally integrated, distributed configurations.MethodsWe performed in vivo two-photon calcium imaging in awake mice to record population activity in V1 during unimodal visual (V) and bimodal visuotactile (V+T) stimulation. From fluorescence time series, we constructed functional connectivity networks and quantified graph-theoretical metrics, including betweenness centrality, closeness centrality, degree centrality, global efficiency, and modularity. Networks were computed per animal and compared across conditions using appropriate non-parametric statistics.ResultsUnimodal visual stimulation increased betweenness centrality and highlighted prominent hub nodes, supporting locally modular, hub-centric information control. In contrast, bimodal visuotactile stimulation elevated closeness centrality and global efficiency, broadened connectivity, and reduced modularity, indicating enhanced global integration with more distributed information flow. Moreover, under unimodal conditions the top five centrality nodes exhibited significantly stronger calcium responses than other neurons, whereas this response hierarchy was abolished under bimodal stimulation.DiscussionV1 dynamically balances local specialization and global integration through context-dependent topological reconfiguration: unimodal processing relies on hub-centric, modular architectures, while cross-modal input promotes globally optimized, distributed networks with higher connectivity efficiency. These findings provide a network-level framework for multisensory integration and offer insights relevant to theories of sensory computation and potential strategies to harness cross-modal plasticity.